1849. Prevalence, Phenotypic and Genotypic Characteristics, and Clinical Presentations of Staphylococcus argenteus Causing Bloodstream Infections in United States Hospitals. (15th December 2022) - Mendes, Rafael; Deshpande, Lalitagauri M; Carvalhaes, Cecilia G; Bell, Drew; Kehl, Sue; Wanger, Audrey; Castanheira, Mariana; Mendes, Rodrigo E
Abstract: Background: Staphylococcus argenteus (SAR) is a novel species within the S. aureus (SAU) complex. SAR has been misidentified as SAU but has been increasingly reported worldwide as a pathogen. This study evaluated the prevalence of SAR causing bloodstream infection (BSI) in US centers, and the phenotypic, genotypic, and clinical outcomes associated with SAR BSI. Methods: 785 SAU (326/459 MRSA/MSSA) from blood cultures (BC) of patients in 31 sites located in all 9 US Census Divisions during the SENTRY Antimicrobial Surveillance Program for 2019 were included. Isolates were screened for SAR by multiplex PCR. Isolates were subjected to MALDI-TOF and susceptibility (S) testing using the CLSI method. Isolates were subjected to genome sequencing, followed by DNA analysis. Results: 0.4% (3/785) SAR were detected and originated from Milwaukee (12 yo female; patient 1), Houston (64 yo male; patient 2), and Seattle (21 yo male; patient 3). Patient 1 had a SAR recovered from BC 10 days after admission, but additional clinical information was not available. Patient 2 had end-stage renal disease and was admitted due to MRSA bacteremia/endocarditis, along with septic embolism in the lungs and brain. SAR grew from BC on day 4 and vancomycin was prescribed; the patient died on day 24. Patient 3 presented fever and chills in the 24 hours pre-admission, with a medical history significant for catheter-associated BSI. SAR was cultured from BC upon admission, and the patient received linezolid (5 days), but BCs remained positive. The central line was removed, and BCs cleared thereafter. MALDI-TOF generated highest scores for SAR for all 3 strains, but scores ≥2.0 were also obtained for SAU and S. schweitzeri . SAR (ST2198) from patient 1 was S to all agents tested, as were the other 2 strains (ST2250 and ST1223), except for oxacillin. The latter 2 strains carried SCC mec type IV(2B) and a dfrG was also detected in the ST2250 lineage strain. All 3 strains carried multiple virulence genes. Conclusion: Low prevalence of SAR causing BSI was observed in US hospitals in 2019; however, SAR can clearly cause invasive infections. ST2250 has predominantly been detected in the USA and Canada, but this study showed distinct lineages causing BSI, including strains carrying mecA and various virulence genes. Disclosures: Rafael Mendes, BS, JMI Laboratory: Grant/Research Support Lalitagauri M. Deshpande, PhD, Melinta: Grant/Research Support|Pfizer: Grant/Research Support Cecilia G. Carvalhaes, MD, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support Mariana Castanheira, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support Rodrigo E. Mendes, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Nabriva Therapeutics: Grant/Research Support|Office for Assistant Secretary of Defense for Health Affairs: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support|Spero Therapeutics: Grant/Research Support.